Tethys’s Heat Fluxes Varied with Time in the Ithaca Chasma and Telemus Basin Region - Chloe B. Beddingfield; Richard J. Cartwright; Sierra N. Ferguson; Erin J. Leonard (The Planetary Science Journal, 2023)
We investigated how lithospheric heat fluxes varied temporally and spatially on the Saturnian moon Tethys, focusing on the region of Ithaca Chasma that overprints Telemus Impact Basin. Our results, derived from flexure associated with Ithaca, indicate elastic thicknesses of 4.1 ± 0.3 km to 6.4 ± 0.4 km and heat fluxes ranging from 12 to 39 mW m ^−2 assuming a nonporous pure H _2 O ice lithosphere. Our results for Ithaca’s south limb are similar to previous estimates within the north limb, indicating consistent heat fluxes across a large spatial extent in this area. However, our estimates are lower than those for the older Telemus Basin (>60 mW m ^−2 ), revealing evidence that Tethys experienced a substantial temporal variation in heat fluxes in this region. Heat fluxes reflected by Ithaca are similar to previous estimates for Tethys’s two youngest impact basins, Melanthius and Odysseus, suggesting that Ithaca may also be relatively young. If Tethys’s lithosphere is porous, then our heat flux estimates for Ithaca Chasma drop to 12–38 mW m ^−2 , 11–35 mW m ^−2 , and 10–33 mW m ^−2 for 5%, 15%, and 25% porosities, respectively. If Tethys’s lithosphere includes ∼10% NH _3 -hydrates, then the estimates are 5–16 mW m ^−2 , 5–15 mW m ^−2 , 4–14 mW m ^−2 , and 4–13 mW m ^−2 for 0%, 5%, 15%, and 25% porosities, respectively. Although we find that some ground-based reflectance spectra hint at 2.2 μ m bands that may result from NH _3 -bearing species, the detected features are weak and may not result from surface constituents. Consequently, our heat flux estimates that assume a pure H _2 O ice lithosphere are likely more accurate.